2008
DOI: 10.1111/j.1745-3933.2008.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

XMM-Newton discovery of transient X-ray pulsar in NGC 1313

Abstract: We report on the discovery and analysis of the transient X-ray pulsar XMMU J031747.5−663010 detected in the 2004 November 23 XMM-Newton observation of the spiral galaxy NGC 1313. The X-ray source exhibits pulsations with a period P ∼ 765.6 s and a nearly sinusoidal pulse shape and pulsed fraction ∼38 per cent in the 0.3-7 keV energy range. The X-ray spectrum of XMMU J031747.5−663010 is hard and well fitted with an absorbed simple power law of photon index ∼ 1.5 in the 0.3-7 keV energy band. The X-ray propertie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…We note that two more extragalactic transient pulsators share striking similarities with the above group, i.e. super-Eddington luminosities and/or large first period derivative, namely XMMU J031747.5-663010 in NGC1313 (∼766 s ;Trudolyubov 2008) and CXOU J073709.1+653544 in NGC2403 (∼18 s; Trudolyubov et al 2007). We suggest here for the first time that they could be two other PULXs that went unnoticed so far.…”
Section: Introductionsupporting
confidence: 53%
“…We note that two more extragalactic transient pulsators share striking similarities with the above group, i.e. super-Eddington luminosities and/or large first period derivative, namely XMMU J031747.5-663010 in NGC1313 (∼766 s ;Trudolyubov 2008) and CXOU J073709.1+653544 in NGC2403 (∼18 s; Trudolyubov et al 2007). We suggest here for the first time that they could be two other PULXs that went unnoticed so far.…”
Section: Introductionsupporting
confidence: 53%
“…Up to now, 7 sources are believed to be ULX pulsars: M82 X-2 [10], NGC 7793 P13 [11,12], NGC 5907 ULX1 [13], NGC 300 ULX1 [14], NGC 1313 X-2 [15], M51 ULX7 [16], and a source within the Milky Way, Swift J0243.6+6124. XMMU J031747.5-663010 in NGC 1313 [17], SMC X-3 [18,19] and M51 ULX8 [20] may also be ULX pulsars. Recently, Song et al [21] identified 25 sources with their flux changes of more than one order of magnitude from 296 ULXs, and claimed these are possible ULX pulsar candidates.…”
Section: Introductionmentioning
confidence: 98%
“…Ultraluminous X-ray sources (ULXs) are extragalactic, non-AGN X-ray sources with luminosities exceeding 10 39 erg s −1 (Kaaret et al 2017). Observations, in a handful of ULXs, of coherent pulsations of ∼ 1 s periodicities (Bachetti et al 2014;Fürst et al 2016;Israel et al 2017a,b;Carpano et al 2018;Motch et al 2014;Fürst et al 2018;Heida et al 2019;Trudolyubov 2008;Doroshenko et al 2018;Tsygankov et al 2017;Townsend et al 2017;Brightman et al 2018) have shown that at least some of these sources are powered by slowly rotating neutron stars accreting above their critical limits, ṀEdd = ηL Edd /c 2 , where η ∼ 0.2 is the binding energy per unit mass at the surface of the neutron star (Syunyaev & Shakura 1986) and L Edd = 4πGM m p c/σ T is the Eddington luminosity of an object with mass, M .…”
Section: Introductionmentioning
confidence: 99%